Búho real – Bubo bubo (Linnaeus, 1758) - Penteriani, Vincenzo; Delgado, María del Mar; Salvador Milla, Alfredo (Salvador Milla, Alfredo, 2016)
Aves - Orden Strigiformes - Familia Strigidae en la Enciclopedia Virtual de Vertebrados Españoles, http://www.vertebradosibericos.org/. Versiones anteriores: 30-03-2010 A comprehensive review of the natural history of the Eurasian Eagle Owl Bubo bubo in Spain. Peer reviewed